The contribution of madrasah principal leadership, teamwork, and work loyalty to the performance of islamic boarding school teachers in manado - Shinta Nento; Abdul Haris Abdullah (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2021)
This study examines theoretical concepts about the contribution of principal madrasa leadership, teamwork, and work loyalty to teacher performance. A survey method is used in a quantitative approach to measure and test structural equation modeling (SEM) using SmartPLS 3.2 software. The population was all Islamic boarding school teachers in Manado City with a sample of 44 respondents. The results showed that teacher performance was influenced by the principal's leadership, teamwork, and job loyalty directly or indirectly. Therefore, the study results recommend that the factors that contribute to teacher performance can be improved or improved in the future.